A double-blind controlled trial of high dose methylprednisolone in patients with multiple sclerosis: 2. Laboratory results. Issue 5 (May 1987) - Compston, D A; Milligan, N M; Hughes, P J; Gibbs, J; McBroom, V; Morgan, B P; Campbell, A K
Abstract : Laboratory measurements were compared in paired samples from 50 patients included in a double-blind placebo controlled trial of methylprednisolone in the treatment of multiple sclerosis. Cerebrospinal fluid total cell count, IgG and C9 indices, and percentage of peripheral blood OKT8 positive cells were abnormal at entry and returned closer to the normal range after active than placebo treatment, but the differences were not statistically significant. The percentage of peripheral blood OKT4 positive cells was normal at entry as was the amplitude of visual evoked potentials, whereas their latency was prolonged; these measurements were each uninfluenced by methylprednisolone. Corticosteroids might act merely by influencing oedema, but the laboratory results suggest that methylprednisolone affects immunological events which underly rapid onset and recovery of symptoms in patients with multiple sclerosis; additional forms of treatment are needed to maintain these clinical and immunological effects.